Cultures of Improvement in Scottish Romanticism, 1707-1840 (Taylor & Francis, 2018)
Cultures; Improvement; Scottish Romanticism
English
Keywords: cultures; improvement; scottish romanticism; thema EDItEUR::D Biography, Literature and Literary studies